If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(2x-1/4)-(x+1)=7(x+2/7)
We move all terms to the left:
4(2x-1/4)-(x+1)-(7(x+2/7))=0
We add all the numbers together, and all the variables
4(+2x-1/4)-(x+1)-(7(+x+2/7))=0
We multiply parentheses
8x-(x+1)-(7(+x+2/7))-1/4*4=0
We get rid of parentheses
8x-x-(7(+x+2/7))-1-1/4*4=0
We calculate fractions
8x-x+(-(7(+x+2*4*4)/()+()/()-1=0
We can not solve this equation
| −1(−19.16b−14)=7.66b−43.5 | | 2x^-5x+20=3x | | 3x-5x=-12+2 | | 28=(x+3)x | | 3x+1/2x+105=108 | | 5×+y=100 | | 8y=6+6 | | 3x+1/2x=180 | | 13x+5=7x-25 | | 3(4x-3)-10x=-19 | | -13.8d-5.9d+10.84=18.36-18.9d | | n2-81=0 | | -16.8t+17.4=-18.5t-16.6 | | 2x=8^3 | | 5(×+y)=100 | | 3t^+24t+6=7t+5 | | 3m+10=m+4 | | -13-2w=-w | | -14q+20=-16q-20+2 | | 2p=1=5 | | 5(2m-6=12 | | -13.4r+8.47=-14.1r | | 13x-8+2x-3=12x-4+2x | | 8x+5-2x+6=15 | | 7x-3=3×+17 | | -18j-19=20-5j | | 3m=5m-8/5. | | -20u+18=-19u | | (9x+2)=(120-9x)-54 | | 3x-23=127 | | 18+10w=-2+11w | | /2m+1÷4-3m+1÷3=2÷3-m |